Oral Health Acquaintance, Approach and Practices among Schoolteachers in Bhopal, Central India - Vanka, Amit; Yadav, Naveen S; Saxena, Vrinda; Sahana, S; Shanti, G; Shivakumar, GC (Journal of Orofacial Research, 2012)
Background: Education of oral health awareness to schoolchildren is important. School teachers can play a major role in imparting knowledge of the causes and prevention of common oral diseases. A school-based program is most effective because children are approached at a time when their health habits are forming. Aims: This study was aimed to assess the acquaintance, approach and practices of schoolteachers toward oral hygiene and oral health in Bhopal city. Materials and methods: Present study is cross-sectional, questionnaire-based , stratified random sampling technique was smeared to obtain the desired sample size. Three hundred and five teachers were selected from 14 different schools of Bhopal city. Results: Around 130 (83.9%) of the teachers of private schools alleged oral health plays an imperative role in general health but 82 (54.7%) of government schoolteachers only agree to foresaid fact regarding oral health and overall health (?2 = 40.294, df = 3, p < 0.001). A total of 96 (61.9%) of the teachers in private and 44 (29.3%) of teachers in government schools used fluoridated toothpaste and 31 (20%) and 40 (26.7%) of the teachers used nonfluoridated toothpaste and the remaining were not concerned about the status of toothpaste, whether fluoridated or nonfluoridated (?2 = 40.722, df = 5, p < 0.001). Conclusion: Teachers essentially need to be invigorated to improve their responsiveness on sound oral health information, approaches and behaviors. This will facilitate their role as school oral health education providers.